THE UNITY OF NATIONALISM AND UNIVERSALISM IN UZBEK MENTALITY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article scientifically analyzes the unity of nationalism and universalism in Uzbek mentality, focusing on the social perceptions, mood, behavioral norms, experiences, knowledge, needs, values, and ideals of the Uzbek people. It explores how all these elements integrate both national and universal aspects. The article examines the influence of national and universal values on social progress, the formation of a new lifestyle, relations with other nations and peoples, social mood, national behavior norms, national experiences, needs, values, and ideals.